MeTIC Award - Alumni Network Category (Best Alumni Collaboration) - UiTM, Faculty of Law (Faculty of Law, 2022)
The Faculty of Law UiTM has received first place for Best Alumni Collaboration for the UiTMLaw Industry-Alumni Mentorship Programme "Inspiring Future Leaders". This event saw alumni of the faculty from different disciplines of the legal industry returning to their alma mater as mentors. They are each assigned to a class to share their knowledge and experience in the professional field. As a result, students are exposed to the real world beyond the academic sphere of their classrooms and will be more prepared to practice law once they conclude their education.